MASALAH-MASALAH YANG DIALAMI ANAK JALANAN DI LAMPU MERAH TABEK GADANG KOTA PEKANBARU - Nugraheni, Novika; Rosmawati, Rosmawati; Donal, Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The phenomenon of poverty in urban areas is one of the effects ofurbanization and mistakes in dealing with population explosion. Poverty problems inurban areas have an impact on the emergence of other social problems. One of them isa street child. Street children are victims of failed government economic policies, streetchildren emerge from economic problems and poverty. Difficulties in the economycause the poor to feel increasingly marginalized and squeezed so they try to find theirown solutions to improve the family's economy. Street children are the same as otherchildren, as normal humans in general they also have problems. The purpose of thisstudy was to determine how the characteristics of the characteristics and problemsexperienced by street children in the Red Light Tabek Gadang Pekanbaru City. Thisresearch is included in a qualitative descriptive study. The subjects of this study were 6people taken using accidental sampling’s technique. The results of the study of 6 streetchildren in the Red Light Tabek Gadang Pekanbaru City characteristics of streetchildren based on their age are between the ages of 16-18 years and all of them areactive as buskers. The problems experienced by street children are problems ofeducation, intimidation, involvement in criminal acts, drug abuse and addictivesubstances, health, work risks, food, and conflicts with parents and family.Key Words: Street Children, Characteristics, Problems.